Digital Marketing And City Branding Analysis Of Tourist Visits: Trust As A Mediation Variable - Sovia, Arina (UPI YPTK Journal of Business and Economics, 2023)
This study aims to test how big the analysis of digital marketing and city branding is on tourist visits to the Thousand Rumah Gadang tourist attraction in Solok Selatan with trust as the intervening variable. Methods of data collection through surveys and distributing questionnaires, with a sample of 100 respondents. The analytical method used is SEM analysis using smartpls. The research results obtained based on hypothesis testing obtained that there is a significant effect of digital marketing on trust. There is a significant influence of city branding on trust. There is a significant influence of digital marketing on tourist visits. There is a significant influence of city branding on tourist visits. There is a significant influence of trust on tourist visits. Trust mediates digital marketing relationships with tourist visits. Trust mediates the relationship between city branding and tourist visits.